High Precision 3D Bio‐printing: Precision 3D‐Printed Cell Scaffolds Mimicking Native Tissue Composition and Mechanics (Adv. Healthcare Mater. 24/2020). Issue 24 (16th December 2020) - Erben, Amelie; Hörning, Marcel; Hartmann, Bastian; Becke, Tanja; Eisler, Stephan A.; Southan, Alexander; Cranz, Séverine; Hayden, Oliver; Kneidinger, Nikolaus; Königshoff, Melanie; Lindner, Michael; Tovar, Günter E. M.; et al.
Abstract : 3D printed cell niches with the highest biological conformity and resolution offer tantalizing avenues for tissue engineering, cell and developmental biology. In article number 2000918 by Stefanie Sudhop, Michael Heymann, and co‐workers, mm‐sized 3D scaffolds with micrometer precision, defined mechanical properties and low autofluorescence are fabricated from extracellular matrix derived gelatin methacryloyl. These scaffolds are compatible with various cell‐lines, including myoblasts colonized on alignment promoting substrates and lung fibroblasts on in vivo derived 3D topographies.